PELATIHAN PENINGKATAN ABSTINENCE SELF EFFICACY PADA PENGGUNA NARKOBA DI PUSAT REHABILITASI - Remila Tuapattinaja, Josetta Maria; irmawati, Irmawati; Saragih, Juliana Irmayanti (Universitas Negeri Surabaya, 2018)
PKM Activities Drug Users are conducted in two institutions in Medan City, which referred as Drug Rehabilitation Center are Narcotics Prevention Rehabilitation Agency (LRPPN) and Rumah Ummi, according to the guidance of the dedication partner of the North Sumatra Narcotics Community Information Center (PIMANSU) each involving 10 drug users from LRPPN and 5 drug users from Rumah Ummi. The problem in both centers is the high number of relapse from drug users because of the lack of attention into build stronger mind and behavior patterns to return to vulnerable communities. This relapse problem can be minimized by increasing abstinence of self efficacy (ASE) that is a belief to refuse using drugs again. Therefore, the main objective and target of PKM Drug Users activities is to enable drug users to face high risk situations through increasing ASE. Target activities include restructuring the irrational mind to be rational as well as understanding the techniques on facing high risk situations. Several methods are used in the achievement of the objectives of field surveys as well as group discussions, frequently asked questions, assignments and reviews. The solutions offered consist of (1) training to recognize the irrational thoughts of drug-related behavior, (2) training to test the truth of the benefits of using drugs, (3) training to recognize high risk situations common to drug users and (4) training using 5 techniques when dealing with situations that potentially trigger relapse.